2017
DOI: 10.1093/ee/nvx201
|View full text |Cite
|
Sign up to set email alerts
|

Field Trapping of Predaceous Insects With Synthetic Herbivore-Induced Plant Volatiles in Cotton Fields

Abstract: Nine herbivore-induced plant volatiles (HIPVs) and one methyl jasmonate were field-tested for their attractiveness to the main predators in cotton fields of North China in 2 yr. The main predators including ladybird beetles (Propylaea japonica (Thunberg), Harmonia axyridis (Pallas)), green lacewings (Chrysoplera sinica (Tjeder), Chrysopa spp.), predatory bugs (Geocoris pallidipennis (Costa), Orius spp., Nabis spp.) and spiders (Misumenops tricuspidatus (Fabricius), Erigonidium graminicolum (Sundevall)) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Our study will support the potential usefulness of nonanal to lure H. axyridis for continuous control before pests, especially aphid outbreaks in crop fields in China. Yu et al (2018) found that indole significantly attracted H. axyridis adults. Next, the synthetic attractants would be developed based on these active compounds.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our study will support the potential usefulness of nonanal to lure H. axyridis for continuous control before pests, especially aphid outbreaks in crop fields in China. Yu et al (2018) found that indole significantly attracted H. axyridis adults. Next, the synthetic attractants would be developed based on these active compounds.…”
Section: Discussionmentioning
confidence: 96%
“…The results of this study are useful for further developing the synthetic attractant of this coccinellid. The use of synthetic volatiles to enhance the recruitment of natural enemies before a pest outbreak might provide a useful pest management tool (James et al 2012;Yu et al 2018), and their use can also suppress the adult population using an attract-and-kill approach in the invasive areas (Verheggen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Verheggen et al (2007) suggested that farnesene was indicated as having potential usefulness in a push-pull method, which repels target pests from a hostplant while luring them towards an attractive trap using H. axyridis as a bio-control agent in aphid infested plants. Furthermore, in a study conducted by Yu et al (2017) linalool attract Propylaea japonica (Thunberg, 1781) (Coleoptera: Coccinellidae). Hence, our field study confirmed that farnesene is considered an important attractant for coccinellids.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the attraction of natural enemies by other synthetic HIPVs has been demonstrated under laboratory and field conditions, and their potential value in pest management has been recognized (James 2005;James and Grasswitz 2005;Kahn et al 2008;Gurr and Kvedaras 2010;Lee 2010;Orre et al 2010). In recent years, field studies have been realized by testing an HIPV (or a mixture of HIPVs) with a trap to determine the diversity and abundance of the attracted natural enemy species (Maeda et al 2015;Lucchi et al 2017;Yu et al 2017). Thus, while the synthetic HIPVs have been tested, there is less work with binary combinations of them in the field conditions.…”
Section: Response Of Aphid Predators To Synthetic Herbivore Induced Pmentioning
confidence: 99%
“…Some synthetic plant volatiles such as methyl salicylate (MeSA) for beneficial insects have been already commercially available (Lee 2010). In China, case of plant volatiles' use is limited and most cases involved predators rather than parasitoids (Yu et al 2008(Yu et al , 2018. Yang et al (2017a) found that MeSA and methyl jasmonate (MeJA) are attractive to E. sophia in the field.…”
Section: Plant Volatiles Influence Parasitoid Waspsmentioning
confidence: 99%